Classification of individuals using handwritten numeral with geometric morphometric techniques - Ismail, Nasrul Hakimie (2020)
No individual will have exactly same handwriting. Handwriting style is something that will acquire and develop through years of learning involving questioned that form individuality. The analysis of handwriting for the purposes of author identification had started since the origin of the handwriting itself. It assisted investigator in crime involving document analysis such as fraud, document falsification and many more. The numbers that used nowadays are also called Hindu- Arabic numbers are combination of 10 digits which are 1,2,3,4,5,,6,7,8,9,and 0. It is a base ten system since the value increases by the power of ten. The handwriting style has very high variations sizes, shapes and fonts. However, the most distinctive characteristics is the shape itself. Geometric morphometric (GMM) is a study of variations in shape. It uses Cartesian geometric coordinates rather than linear, area or volumetric variables. The basis of the technique is coordinates of identifiable landmarks (LM) and semilandmarks (SL) to capture the image shape. In this project, 200 samples of consisting of numeral 1, 6, 8 and 9 were collected from 10 students of Universiti Sains Malaysia (USM). The number is based on previous study by Tay Eue Kam (2019), as it successfully used in ethnic discrimination by using fully manual method based on slant, width and height measurement. The PCA of PC1 and PC2 shows cumulative variance percentage for numeral 1, 6, 8 and 9 were 100.00%, 67.59%, 56.34% and 65.17% respectively. Numeral 6 was the only numerals that show significant differences between individuals. Geometric morphometric is useful in individual identification based on shape of the numerals.